Do Financially Distressed Firms Engage in Earnings Management? The Role of IFRS Mandatory Adoption in Emerging Markets - Viana, D. B. C., Jr.; Lourenço, I.; Black, E. L. (2020 Grudis Conference & Doctoral Colloquium, 2020)
This study examines whether financially distressed firms from emerging markets are associated with a higher level of accrual-based (AEM) and real earnings management (REM) than their counterparts, and how this relationship compares between pre- and post- mandatory adoption of International Financial Reporting Standards (IFRS) in those markets. Based on an international sample of 7,473 firm-year observations from 15 emerging markets, we predict and find that financially distressed firms overall engage in more AEM and REM than non-financially distressed firms. Furthermore, our results also suggest that IFRS mandatory adoption decreases earnings management levels of distressed firms, but only with AEM; there is no statistical effect on REM. Our findings contribute to the empirical research on financial distress and earnings management, especially demonstrating the role of IFRS adoption in emerging markets by inhibiting AEM in distressed firms. Additionally, we significantly enhance international accounting research, demonstrating the challenges of financially distressed firms to engage in a potential trade-off between AEM and REM, as commonly suggested in previous literature on earnings management.